EMBR-03. TREATMENT OF EMBRYONAL TUMOR WITH MULTILAYERED ROSETTES (ETMR) WITH TARGETED RADIOIMMUNOTHERAPY. Issue 2 (22nd June 2018) - Bailey, Kayleen; Pandit-Taskar, Neeta; Humm, John; Zanzonico, Pat; Gilheeney, Stephen W; Kramer, Kim
Abstract: PURPOSE: Embryonal Tumor/Multilayered Rosettes (ETMR) is an aggressive CNS tumor in young children; median survival is 12 months. We explored the use of intraventricular 131 I-8H9 targeting B7-H3 in patients with ETMR on a trial at MSK. METHODS: Patients received 2 mCi 131 I-8H9 as a tracer followed by 1 or 2 therapeutic 131 I-8H9 injections. Dosimetry was based on serial CSF, blood samplings and region of interest (ROI) on nuclear scans. Brain and spine MRIs and CSF cytology were done at baseline, 5 weeks after 131 I-8H9, and approximately every 3 months thereafter. Acute toxicities and survival were noted. RESULTS: Three symptomatic children (ages 14 months, 3 and 3.5 years) had large parietal masses confirmed to be B7-H3+ ETMR. Patients received surgery, focal radiation, and high dose chemotherapy. Patients 1 and 2 received 131 I-8H9 (80 and 53 mCi, respectively). Patient 3 had a local recurrence prior to 131 I-8H9 treated with surgery, craniospinal radiation, chemotherapy, then 131 I-8H9 (36 mCi). 131 I-8H9 was well-tolerated; patient 2 had grade 4 thrombocytopenia 1 month after injection. Mean dose delivered by 131 I-8H9 was 68.4 cGy/mCi to CSF and 1.95 cGy/mCi to blood. Mean ROI doses were 230.4 (ventricular) and 58.2 (spinal) cGy/mCi. Patients 1 and 2 remain in remission 5.5 and 1.2 years after diagnosis, respectively. Patient 3 suffered a third local recurrence 22 months after diagnosis and remains alive with disease. CONCLUSIONS: 131 I-8H9 appears safe with favorable dosimetry therapeutic index. When used as consolidation following surgery and chemoradiation therapy, 131 I-8H9 may have therapeutic benefit for patients with ETMR.